Low-dose letrozole-HMG regimen reverses letrozole-induced endometrial impairment and improves frozen embryo transfer outcomes - Xiao, Zhonglin; Wang, Feng; Yang, Yali; Xiao, Tianxia; Chen, Jie; Li, Mengxia; Liao, Haizhen; Chu, Chiawei; Fan, Xiujun; Zhang, Jian V. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionLetrozole monotherapy, while effective for ovulation induction, may compromise endometrial receptivity in frozen embryo transfer (FET) cycles due to estrogen suppression. This study aimed to compare the FET outcomes and analyze the molecular mechanisms of endometrial receptivity among low-dose letrozole plus HMG (LeH) with letrozole monotherapy (Le) and natural cycles (NC).MethodsThis retrospective cohort study included 5,673 infertile patients undergoing FET with one of the following protocols: LeH (n = 2,997), Le (n = 1,762), or NC (n = 914). Endometrial receptivity was assessed via serum hormone assays, scanning electron microscopy (SEM) of pinopodes on post-ovulation days 3 (D3; pre-FET) and 5 (D5; estimated implantation window), and proteomic analyses of endometrial tissue, uterine fluid, and serum on D3.ResultsClinical outcomes revealed that the LeH group had significantly higher implantation, clinical pregnancy and live birth rates compared to the Le and NC groups, especially among older women. Notably, the Le group was associated with thinner endometrium, lower estradiol levels, reduced vascularization flow index (VFI), and a lower proportion of receptive-phase endometria (28% vs. 60% in NC). In contrast, the LeH group maintained normal endometrial parameters, and resulted in a high proportion of fully developed pinopodes (84%). Proteomic profiling revealed that the Le group adversely affected processes related to cell adhesion and inflammatory regulation, while the LeH group reversed these alterations. It activated pathways important for embryo implantation and promoted an anti-inflammatory environment.DiscussionThese results suggest that the LeH regimen may mitigate letrozole-induced endometrial impairment and enhances FET outcomes through structural, molecular, and immunological mechanisms, offering a promising approach for optimized endometrial preparation.